Studying m6A in the brain: a perspective on current methods, challenges, and future directions - Tegowski, Matthew; Meyer, Kate D. (Frontiers in Molecular Neuroscience, 2024)
A major mechanism of post-transcriptional RNA regulation in cells is the addition of chemical modifications to RNA nucleosides, which contributes to nearly every aspect of the RNA life cycle. N6-methyladenosine (m6A) is a highly prevalent modification in cellular mRNAs and non-coding RNAs, and it plays important roles in the control of gene expression and cellular function. Within the brain, proper regulation of m6A is critical for neurodevelopment, learning and memory, and the response to injury, and m6A dysregulation has been implicated in a variety of neurological disorders. Thus, understanding m6A and how it is regulated in the brain is important for uncovering its roles in brain function and potentially identifying novel therapeutic pathways for human disease. Much of our knowledge of m6A has been driven by technical advances in the ability to map and quantify m6A sites. Here, we review current technologies for characterizing m6A and highlight emerging methods. We discuss the advantages and limitations of current tools as well as major challenges going forward, and we provide our perspective on how continued developments in this area can propel our understanding of m6A in the brain and its role in brain disease.